Switchable Terahertz Band-Pass/Band-Stop Filter Enabled by Hybrid Vanadium Dioxide Metamaterial - Ying Chen; Jianwei Cheng; Chaowu Liang (Advances in Condensed Matter Physics)
To date, little research has been carried out on the integration of switchable and diversified functionalities into a single metamaterial in the terahertz (THz) range. Here, a hybrid vanadium dioxide (VO2) metamaterial was designed with switchable properties of band-pass filter and band-stop filter in the frequency range of 0.3–1.6 THz. Simulations demonstrated that under TE polarization, the proposed system acted as band-stop filter with the center frequency of 0.95 THz when VO2 is in the insulating state. Upon the transformation of VO2 into the metallic state, the proposed system behaved as a band-pass filter with a transmittance of >80%. The physical mechanism of the band-pass/band-stop conversion was examined by analyzing the surface current distribution of the designed device. The switchable characteristics of this structure can enable its wide application in tunable THz functional components such as amplitude modulators, polarization control, and intelligent switches.